Policies in the Context of Humanitarian Emergencies Involving Persons with Disabilities - Simard, Mathieu (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2009)
This paper presents a non-systematic review discussing the representation of people with disabilities (PWDs) in humanitarian emergency policies. This review found a difference between disabilityfocused organizations and organizations not focused on disability. Those not focusing on disability tend not to directly mention PWDs as being a target group for their action. They also present PWDs in a more passive or victimizing role.This may be influenced by differences in organisational culture, as well as by contextual differences in the creation of the non-governmental organizations (NGO’s). NGO’s that have existed for a long time were most commonly created in a charitable or a medical model, whereas more recently created organizations tend to be based on a rights oriented model.Solutions proposed to counteract this problem include involving PWDs and disability advocacy NGOs in all steps of the analysis, planning, policy development, implementation, response and relief, rehabilitation and reconstruction. PWDs should be involved in disaster activities which would in turn allow for a better inclusion of persons with disability in policies and in relief efforts.